Family Communication Strategy to Improve Gender Equality for Girls in Coastal of South Sulawesi Province (Strategi Komunikasi Keluarga untuk Meningkatkan Kesetaraan Gender bagi Anak Perempuan di Kawasan Pesisir Provinsi Sulawesi Selatan) - Fatimah, Jeanny Maria (Jurnal Pekommas, 2016)
Education coastal communities still need serious attention, because girls do not become a priority for continuing education. Assuming that the boy would become head of the family, in charge of the family and became a central figure in the family community. The family is the central point to provide gender equality for girls to pursue higher education is equal to boys through family communication approach. The purpose of this study was to understand the communication strategy of the family in promoting gender equality for girls in the coastal areas. The research method used mixed-method research that combines qualitative and quantitative research. Sources of data become the subject of research are the parents and the girls, then the data through observation, interviews, and questionnaires.Research shows that family communication strategy to promote gender equality girls in coastal areas is the context of communication between parents and children as an effort to change cultural stereotypes of ethnic Bugis and poverty. Family communication strategy refers to the communication patterns of openness, empathetic attitude, supportive attitude, a positive attitude and the attitude of equality in communication of family members for the sake of equality and fairness girls. Based family communication strategy for the achievement of gender equality more viable livelihoods and improving the welfare of poor families living on the coast of South Sulawesi.Pendidikan masyarakat pesisir masih memerlukan perhatian serius, dikarenakan anak perempuan tidak menjadi proritas untuk melanjutkan pendidikan. Asumsi bahwa anak laki-laki menjadi kepala keluarga, penanggung jawab keluarga dan menjadi figur sentral dalam komunitas keluarga. Keluarga merupakan titik sentral untuk memberikan kesetaraan gender bagi anak perempuan untuk melanjutkan pendidikan tinggi setara dengan anak laki-laki melalui pendekatan komunikasi keluarga. Tujuan penelitian ini adalah memahami strategi komunikasi keluarga dalam meningkatkan kesetaraan gender bagi anak perempuan di daerah pesisir. Metode penelitian menggunakan kualitatif deskriptif. Metode kualitatif jenis studi kasus (case study).Sumber data sekaligus subjek penelitian adalah orang tua dan anak perempuan.  Selanjutnya teknik pengumpulan data melalui observasi, wawancara mendalam, dan kuesioner. Hasil Penelitian menunjukkan bahwa strategi komunikasi keluarga untuk meningkatkan kesetaraan gender anak perempuan di kawasan pesisir pantai merupakan konteks komunikasi antara orangtua dan anak sebagai upaya perubahan stereotipe budaya etnik Bugis dan faktor kemiskinan. Strategi komunikasi keluarga merujuk pada pola komunikasi keterbukaan, sikap empatik, sikap mendukung, sikap positif dan sikap kesetaraan dalam berkomunikasi anggota keluarga demi kesetaraan dan keadilan anak perempuan.  Strategi komunikasi keluarga berbasis keadilan gender untuk pencapaian penghidupan yang lebih layak dan peningkatan kesejahteraan hidup keluarga miskin di pesisir pantai Sulawesi Selatan. Education coastal communities still need serious attention, because girls do not become a priority for continuing education. Assuming that the boy would become head of the family, in charge of the family and became a central figure in the family community. The family is the central point to provide gender equality for girls to pursue higher education is equal to boys through family communication approach. The purpose of this study was to understand the communication strategy of the family in promoting gender equality for girls in the coastal areas. The research method used mixed-method research that combines qualitative and quantitative research. Sources of data become the subject of research are the parents and the girls, then the data through observation, interviews, and questionnaires.Research shows that family communication strategy to promote gender equality girls in coastal areas is the context of communication between parents and children as an effort to change cultural stereotypes of ethnic Bugis and poverty. Family communication strategy refers to the communication patterns of openness, empathetic attitude, supportive attitude, a positive attitude and the attitude of equality in communication of family members for the sake of equality and fairness girls. Based family communication strategy for the achievement of gender equality more viable livelihoods and improving the welfare of poor families living on the coast of South Sulawesi.